Perkembangan identiti kaum Peranakan Samsam Islam: Satu kajian kes seorang Dalang Wayang Gedek di Kedah - Sohaimi Abdul Aziz,; Omar Yusoff, (Universiti Kebangsaan Malaysia, 2010)
This article discusses the identity development of the Peranankan Samsam Malay-Muslim community in the northern state of Kedah today. This study adopts the historical and anthropological approaches. The research methodology is based on non-structured interviews, library research and textual analysis. The Peranakan Samsam Malay-Muslim is a minority descended from Siam (Thailand). They are here since the 18th century. From the start, their presence is not fully accepted by the local Malay ethnic as a true Malay- Muslim because they are believed to practice the norms which are against the practice of Islam. This feature, form their identity and it makes the Peranakan Samsam Muslim negatively labeled. This article discovered that the negative identity has changed to the better because of the assimilation of the community with the local Malay-Muslim which has been going on since the implementation of the New Economy Policy in 1970s. Nevertheless, the negative identity could still be identified among the peranakan community but the number is scarce. A well-known ‘dalang’ (puppet master) of the Wayang